Simulation Technology Research on the Brake Control Unit of Rolling Stocks - LU Jinjun; LIU Yinhu; YANG Lei (机车电传动)
In order to improve the development efficiency and quality of brake control unit, an integrated design method based onsimulation technology was proposed. With the introduction of brake system composition and brake control unit operation principles,based on the design method, simulation modeling and off-line simulation of brake control unit and the controlled object was realized, aswell as the rapid control prototype (RCP) and the hardware-in-the-loop simulation (HILS) of brake control unit, which implemented thedevelopment and tests of brake control unit. The test result presents the fulfillment of the brake control unit, and verifies the effectivenessof the design method based on simulation technology.